C∞-regularity of non-Lipshitz heat semigroups on noncompact Riemannian manifolds - Antoniouk, A.Val. (Інститут прикладної математики і механіки НАН України, 2008)
We obtain the applications of approach [2, 5, 6] to the high order regularity of solutions to the parabolic Cauchy problem with globally non-Lipschitz coeffcients growing at the in nity of a noncompact manifold. In comparison to [2], where the semigroup properties were studied by application of nonlinear estimates on variations with use of local arguments of [11], i.e. for manifolds with the C² metric distance function, the developed below approach works for the general noncompact manifold with possible non-unique geodesics between distant points.